Tanner '88 [videorecording (DVD)] - Altman, Robert, 1925-2006; Murphy, Michael, 1938-; Reed, Pamela; Nixon, Cynthia (Criterion collection, 2004)
During the 1988 presidential campaign, Democratic hopefuls spiritedly canvass the country, jostle for their party's nomination and the honor of opposing Republican Vice President George Bush. Then Senator Jack Tanner suddenly emerges from the shadows of a lengthy political hiatus to challenge candidates such as Al Gore, Jesse Jackson, Gary Hart, and Michael Dukakis. Tanner is a fictitious presidential candidate who goes out on the campaign trail to shed light on America's political process and landscape.